2020
DOI: 10.1093/jas/skz375
|View full text |Cite
|
Sign up to set email alerts
|

Torula yeast has greater digestibility of amino acids and phosphorus, but not energy, compared with a commercial source of fish meal fed to weanling pigs

Abstract: Three experiments were conducted to test the hypothesis that the standardized ileal digestibility (SID) of AA, concentrations of DE and ME, and the standardized total tract digestibility (STTD) of P in a source of torula yeast are not different from values obtained in Menhaden fish meal. In experiment 1, six weanling barrows (initial BW: 11.7 ± 0.4 kg) were prepared with a T-cannula in the distal ileum and allotted to a replicated 3 × 3 Latin square design with 3 diets and 3 periods. In each period, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
9
12
0
Order By: Relevance
“…The analyzed CP, AA, and ash concentrations in FM are consistent with the previously reported values [ 9 , 14 , 15 ]. In addition, the concentration of AEE in FM also agrees with the values reported in Casas et al [ 14 ] and Lagos and Stein [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The analyzed CP, AA, and ash concentrations in FM are consistent with the previously reported values [ 9 , 14 , 15 ]. In addition, the concentration of AEE in FM also agrees with the values reported in Casas et al [ 14 ] and Lagos and Stein [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…The analyzed CP, AA, and ash concentrations in FM are consistent with the previously reported values [ 9 , 14 , 15 ]. In addition, the concentration of AEE in FM also agrees with the values reported in Casas et al [ 14 ] and Lagos and Stein [ 15 ]. The FM used in the current study is representative due to similarity in AA concentration for FM reported in previous studies [ 9 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thiamin content of a dried brewer's torula yeast was 6.7 mg/kg DMB [1], which was lower than all six yeast ingredients screened in the present experiment. Crude protein and fat contents of all 6 yeasts fell in line with ingredients evaluated in animal feeding experiments [15,[27][28][29]. The FP ingredient contained notably high levels of crude fiber compared to the other yeast ingredients, which was expected.…”
Section: Plos Onesupporting
confidence: 55%